A concept of overlapping meshless FEM and its application in experimental mechanics - Karmowski, Wojciech (Computer Assisted Methods in Engineering and Science; Vol 8 No 4 (2001), 2023)
In the paper a new meshless FEM method is proposed. The method is physically based and the defined element ensures agreement with equilibrium equations. A special functional is defined which consist of a smoothing term, a boundary term and eventually an experimental one. In one calculation both theoretical and experimental data are used to establish proper solution. The method may be used even in the case when constitutive equation is unknown, what is especially important for residual stress problems.